IMPLEMENTASI MODEL LEARNING CYCLE â€œ5Eâ€ DISERTAI LKS UNTUK MENINGKATKAN AKTIVITAS, KETERAMPILAN PROSES SAINS, DAN HASIL BELAJAR BIOLOGI - Purwanto, Ahmad (BIOEDUKASI (Jurnal Pendidikan Biologi), 2014)
This research aims to implement the model learning cycle "5E" accompanied by worksheets to increase activity, science process skills and student learning outcomes. This model provides student involvement and hands-on experience for students, develop a collaborative manner with the group and share your knowledge with other students. Conclusions of this study is the implementation model of learning cycle "5E" with worksheets may enhance the activity, science process skills, and student learning outcomes of X8 in the second semester at senior high school 4th Metro on academic year 2011/2012. The increase can be observed as follows: the activity of reading the literature by 23%, experiment activity (drawing objects of observation) by 25%, in a group discussion activity by 23%, the activity of asking questions by 17%, and argues activity by 10%. In the process skills of science students on aspects of the skill increased by 25% using the tool, the object classifies 30%, the cooperation within the group by 22%, delivering the acquisition of 23%. Learning outcomes of students has increased by 4% which is in cycle I of 71% to 75% in cycle II. As for the improvement of pre-survey to cycle II by 56% which is 19% in pre-survey become to 75% in Cycle II. Kata kunci: model learning cycle "5E" disertai LKS, aktivitas belajar, keterampilan proses sains, hasil belajar